Mutation analysis of the promoter region of CYBRD1, HFE, LTF, HAMP and SLC40A1 in a Tuberculosis cohort - Sittmann, Margarete (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.